2007
DOI: 10.1007/s00114-007-0320-5
|View full text |Cite
|
Sign up to set email alerts
|

Postautotomy tail activity in the Balearic lizard, Podarcis lilfordi

Abstract: Caudal autotomy is an effective antipredator strategy widespread among lizards. The shed tail thrashes vigorously for long periods to distract the predator and facilitate the lizard's escape. This movement is maintained by energy supplied by the anaerobic conversion of glycogen into lactate. It has been suggested that lactate accumulation serves as an index for the vigor of tail thrashing. We made three predictions: (1) tail loss frequency should be higher under heavier predation regime, (2) the duration of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 25 publications
(33 reference statements)
2
14
2
3
Order By: Relevance
“…Researchers have long debated whether the highest incidences of autotomy should occur in areas with inefficient predators (because failed attacks are likely to result in autotomy and escape), or areas with the greater diversity of predators (Cooper et al ; Pafilis et al ; Bateman and Fleming ; reviewed in Bateman and Fleming ). In contrast to other studies on Mediterranean herpetofauna (Diego‐Rasilla ; Cooper et al ; Pafilis et al , ), we found that field autotomy rates did not reflect prevailing predation levels (in terms of predator diversity), nor were they correlated with standardized laboratory autotomy trials. Counterintuitively, the highest rates of autotomy were actually observed on islets completely isolated from predators, suggesting that autotomy on predator‐free islets was driven by intraspecific aggression and not by predation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Researchers have long debated whether the highest incidences of autotomy should occur in areas with inefficient predators (because failed attacks are likely to result in autotomy and escape), or areas with the greater diversity of predators (Cooper et al ; Pafilis et al ; Bateman and Fleming ; reviewed in Bateman and Fleming ). In contrast to other studies on Mediterranean herpetofauna (Diego‐Rasilla ; Cooper et al ; Pafilis et al , ), we found that field autotomy rates did not reflect prevailing predation levels (in terms of predator diversity), nor were they correlated with standardized laboratory autotomy trials. Counterintuitively, the highest rates of autotomy were actually observed on islets completely isolated from predators, suggesting that autotomy on predator‐free islets was driven by intraspecific aggression and not by predation.…”
Section: Discussioncontrasting
confidence: 99%
“…Lowered social status (Fox and Rostker ; Schall et al ; Salvador et al ) and decreased reproductive output are additional transient, negative effects incurred by recently autotomized individuals (Ballinger and Tinkle ; Vitt and Cooper ; Pafilis et al ; Cromie and Chapple ). Because autotomy can occur accidentally and without survival benefit during intraspecific interactions (Vitt et al , Jennings and Thompson ; Pafilis et al ; Vervust et al ), ease of autotomy in a population should reflect associated costs and benefits.…”
mentioning
confidence: 99%
“…However, lizards may also shed their tails as a consequence of intraspecific aggression (Langkilde & Shine ; Pafilis et al. ). Field observations are in accordance with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Of all the courtship encounters they observed 85.7% were initiated by blue males, vs. 7.1% initiated by brown males and 7.2% initiated by females. Individuals of a translocated population of St. Lucia whiptail Cnemidophorus vanzoi on Praslin Island [70] evolved increased growth rates, and high intensity of intraspecific competition (see also [37,71,72] on Balearic Podarcis lilfordi and on Skyros archipelago Podarcis gaigeae ). Praslin whiptails also have increased sexual size dimorphism and sexual dichromatism.…”
Section: Discussionmentioning
confidence: 99%